The algorithm of search and identification of Internet sources on historical events - Peleshchyshyn, Andriy; Bilushchak, Тetiana (Lviv Polytechnic Publishing House, 2016)
The paper presents the results of creating the algorithm of search and identification of Internet sources on historical events for efficient work of researchers of history.
Keywords: algorithm of search; Internet sources; historical events; social networks; Facebook; consolidated information resource; search parameters; verification; establishing authorship; algorithm detalisation